Adolescents' perspectives regarding their communication with reproductive health service providers in Rwanda: an explorative study - Josephine Uzayisenga; Augustin Nshimiyimana; Gerard Kaberuka; Marie Laetitia Ishimwe Bazakare; Valens Mbarushimana; Madeleine Mukeshimana; Aimable Musafili; Laetitia Nyirazinyoye (BMC, 2024)
Abstract Background Adolescents in low-middle-income countries often face limited access to health information and services due to several different factors. Ineffective communication between healthcare providers and adolescents is among them. This study aims to assess adolescents' perspectives regarding their communication with reproductive health service providers in Rwanda. Methods A phenomenological exploratory qualitative study was used. Eleven focus group discussions were conducted among adolescents aged 10 to 19 years between December 2020 and January 2021. All participants were identified through their respective health care providers in youth-friendly centres available in the Kigali district representing the urban area and Kamonyi district representing the rural area. All interviews were transcribed and translated into English and analysed by using thematic content analysis. Results Poor communication between healthcare providers and adolescents was identified and attributed to the judgmental attitudes of some healthcare providers, while good communication was cited by many adolescents as an important key of access to services. All adolescents were eager to access reproductive health services and be educated about reproductive health issues. Conclusion Effective communication is essential when it comes to providing reproductive health services, as this establishes a strong relationship between a service provider and an adolescent who wants to talk about their concerns, while poor communication prevents adolescents from asking questions about unknown topics.